Architecture, form, space & order - Ching, Frank, 1943- 4 0 16; 5 (New York : Van Nostrand Reinhold, 1979)
Illustrations and text help demonstrate the major principles of form, space, and order in architecture, including line, point, plane, scale, and volume.
Includes bibliographical references (p. 377) and indexes.
Adult;Adult.
Keywords: 2 -- 0; 6; Composition, proportion, etc. -- Architecture;Space (Architecture);Architecture.;Perception.; 20; 2